Purinergic and Store-Operated Ca2+ Signaling Mechanisms in Mesenchymal Stem Cells and Their Roles in ATP-Induced Stimulation of Cell Migration. (14th April 2016) - Peng, Hongsen; Hao, Yunjie; Mousawi, Fatema; Roger, Sebastien; Li, Jing; Sim, Joan A.; Ponnambalam, Sreenivasan; Yang, Xuebin; Jiang, Lin-Hua
Abstract: ATP is an extrinsic signal that can induce an increase in the cytosolic Ca 2+ level ([Ca 2+ ]c ) in mesenchymal stem cells (MSCs). However, the cognate intrinsic mechanisms underlying ATP-induced Ca 2+ signaling in MSCs is still contentious, and their importance in MSC migration remains unknown. In this study, we investigated the molecular mechanisms underlying ATP-induced Ca 2+ signaling and their roles in the regulation of cell migration in human dental pulp MSCs (hDP-MSCs). RT-PCR analysis of mRNA transcripts and interrogation of agonist-induced increases in the [Ca 2+ ]c support that P2X7, P2Y1, and P2Y11 receptors participate in ATP-induced Ca 2+ signaling. In addition, following P2Y receptor activation, Ca 2+ release-activated Ca 2+ Orai1/Stim1 channel as a downstream mechanism also plays a significant role in ATP-induced Ca 2+ signaling. ATP concentration-dependently stimulates hDP-MSC migration. Pharmacological and genetic interventions of the expression or function of the P2X7, P2Y1 and P2Y11 receptors, and Orai1/Stim1 channel support critical involvement of these Ca 2+ signaling mechanisms in ATP-induced stimulation of hDP-MSC migration. Taken together, this study provide evidence to show that purinergic P2X7, P2Y1, and P2Y11 receptors and store-operated Orai1/Stim1 channel represent important molecular mechanisms responsible for ATP-induced Ca 2+ signaling in hDP-MSCs and activation of these mechanisms stimulates hDP-MSC migration. Such information is useful in building a mechanistic understanding of MSC homing in tissue homeostasis and developing more efficient MSC-based therapeutic applications. Abstract : iATP as an extrinsic signal activates purinergic P2X7, P2Y1 and P2Y11 receptors on mesenchymal stem cell (MSC) derived from human dental pulp. Activation of the P2Y1 and P2Y11 receptors stimulates phospholipase C (PLC) via the Gα, 11 protein, leading to production of IP3 from the membrane lipid PIP2, IP3 receptor (IP3 R)-mediated Ca 2+ release from the endoplasmic reticulum (ER) and STIM1-dependent gating of the Orai1 channel. ATP can also activate the P2X7 receptor ion channel. Both Orai1 and P2X7 channels mediate extracellular Ca 2+ influx, resulting in an increase in the cytosolic Ca 2+ level. Such ATP-induced Ca 2+ signalling mechanisms promote MSC migration.